Cloud native Java designing resilient systems with Spring Boot, Spring Cloud, and Cloud Foundry - Long, Josh; Bastani, Kenny (O'Reilly Media, 2017)
Learn the essentials of the Spring Boot microframework for developing modern, cloud-ready JVM applications and microservices across a variety of environments. With this practical book, you'll learn everything you need to know to get started working with Spring Boot.